2023
DOI: 10.1002/ohn.197
|View full text |Cite
|
Sign up to set email alerts
|

Layperson Perception of Symptoms Caused by the Sinuses

Abstract: Objective To assess the perceived symptoms caused by the sinuses as defined by otolaryngology patients and clinicians. Study Design Multi‐institutional cross‐sectional study. Setting Six academic outpatient otolaryngology practices. Methods We performed a multi‐institutional, cross‐sectional study using a semantics‐based questionnaire. Consecutive patients were enrolled at 6 academic otolaryngology centers from June 2020 to May 2021. The primary outcome examined patient and provider definitions for the symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Prior studies have demonstrated significant differences between patients and clinicians in the verbiage used to describe other common otolaryngologic complaints such as congestion, 7,8 reflux, 9 and sinus infections. 10,11 Dizziness has also been previously evaluated at a single institution, where there was found to be significant differences in how patients and clinicians define this common complaint. 12 No multi-institutional study has been conducted to date on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated significant differences between patients and clinicians in the verbiage used to describe other common otolaryngologic complaints such as congestion, 7,8 reflux, 9 and sinus infections. 10,11 Dizziness has also been previously evaluated at a single institution, where there was found to be significant differences in how patients and clinicians define this common complaint. 12 No multi-institutional study has been conducted to date on the topic.…”
Section: Introductionmentioning
confidence: 99%